Hybrid renewable energy systems in remote areas of equatorial countries - Nejad, Mohsen Fadaee; Mohd Radzi, Mohd Amran; Ab Kadir, Mohd Zainal Abidin; Hizam, Hashim (IEEE, 2012)
Traditional power systems for remote or rural areas are based on fossil fuels. After implementation of renewable energy (RE) resources, solar energy applications have become popular in remote energy systems. The recent research works show that the combination of some other RE resources such as wind and hydro could make a power system more cost-effective and environmental friendly. Besides that, hybrid renewable energy systems for rural electrifications have grown rapidly in recent years. In the present study, an overview of applied HRESs for rural areas is presented to help present and future works in this field. Hence, a large number of papers was reviewed and analyzed. The findings show that the proper HRES in general for villages in equatorial countries is PV-wind based system.